Dialogical writing: Co-inquiring between the written and the spoken word. Issue 1 (1st January 2019) - Helin, Jenny
ABSTRACT: The foundational view of discourse as a descriptive mode of representation and writing as a retrospective stabilizing tool has been criticized in organization and management research. The purpose of this paper is to inquire into a more emergent, unfinished, and relational writing used throughout the research processes. To that aim, I develop the notion of 'dialogical writing' by drawing on the literature on performative utterances and a collaborative fieldwork project where writing became an integrated part of the research process. I come to understand this form of writing as one in situ where addressivity, responsiveness, and unfinalizability are emphasized. This enables writing to be part of a conversation; writing as a response to that which has been said and in anticipation of the next possible utterance. I close with implications for writing in organization studies, such as the possibility of thinking of writing as an offering of the tentative.